2013
DOI: 10.1063/1.4836795
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium energy spectrum in the subgrid-scale one-equation model in large-eddy simulation

Abstract: The subgrid-scale (SGS) modeling in large-eddy simulation (LES) which accounts for the effect of unsteadiness and nonequilibrium state in the SGS is considered. Unsteadiness is incorporated by considering the spectral evolution in the forced homogeneous isotropic turbulence using the transport equation for the SGS energy. As for the unfiltered spectrum, perturbative expansion of the Kovasnay spectral model about the Kolmogorov −5/3 energy spectrum which constitutes a base equilibrium state in the inertial subr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
5
18
0
Order By: Relevance
“…We reproduce a simple derivation of the non-equilibrium correction here. The same results were obtained by [23,24] using similarity arguments, using Kovaznay's closure in [25] and using more sophisticated closures in [22,26].We start from the evolution equation for the kinetic energy spectrum at high Reynolds numbers at scales where both production and dissipation mechanisms can be ne-arXiv:1610.04054v1 [physics.flu-dyn]…”
mentioning
confidence: 81%
“…We reproduce a simple derivation of the non-equilibrium correction here. The same results were obtained by [23,24] using similarity arguments, using Kovaznay's closure in [25] and using more sophisticated closures in [22,26].We start from the evolution equation for the kinetic energy spectrum at high Reynolds numbers at scales where both production and dissipation mechanisms can be ne-arXiv:1610.04054v1 [physics.flu-dyn]…”
mentioning
confidence: 81%
“…If we carefully visit the regions of coherent structures, it can be found that none of these assumptions is satisfied: i) the Reynolds number may be not high (usually Re λ < 1000), which does not lead to obvious inertial range [27]; ii) the flow is usually inhomogeneous; iii) the local isotropy is not usually satisfied even in small scales; iv) the flow is in non-equilibrium. Existing studies have focused on and (partly) solved the first three problems [27][28][29][30][31][32][33][34], however, there is still few attempts on the fourth problem, i.e., the non-equilibrium fact, in the domain of SGS modeling [35,7]. In this case, in the following we would like to introduce our previous attempt of considering the non-equilibrium in a simplest situation, i.e., the homogeneous isotropic turbulence (HIT).…”
Section: Definition Of Spectral Non-equilibrium Property In Homogeneomentioning
confidence: 97%
“…However, LES simulations for capturing largescale coherent structures (e.g., separation, transition and boundary layer) do not usually yield satisfactory results, while some of them are even worse than the Reynolds-averaged Navier-Stokes (RANS) results [4]. This bad performance also happens in the nonequilibrium regions, even if the flow is free from boundaries [5][6][7][8][9]. Various attempts have been performed to repair this problem.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This will then reflect the topology of the flow under consideration, permitting phase lags as a consequence of local variations in dissipation. Perhaps more importantly for representing complex processes, it will, as a consequence, permit reverse cascades of energy whereby subfilter scale energy generation can sustain large-scale oscillation, which is more realistic than the absolutely dissipative Smagorinsky approach [Horiuti and Tamaki, 2013]. Such a model may also be implemented within the dynamic framework [Ghosal et al, 1995] and, hence, the triple filtering approach of Porte-Agel and coworkers [Porte-Agel et al, 2000;Bou-Zeid et al, 2005] described above, providing significant greater flexibility in the evaluation of the modeling coefficients.…”
Section: A Route To a Nonequilibrium Modeling Frameworkmentioning
confidence: 99%